2017
DOI: 10.1002/2016gl071891
|View full text |Cite
|
Sign up to set email alerts
|

Boiling and condensation of saline geothermal fluids above magmatic intrusions

Abstract: Numerical simulation of subaerial, magma‐driven, saline hydrothermal systems reveals that fluid phase separation near the intrusion is a first‐order control on the dynamics and efficiency of heat and mass transfer. Above shallow intrusions emplaced at <2.5 km depth, phase separation through boiling of saline liquid leads to accumulation of low‐mobility hypersaline brines and halite precipitation, thereby reducing the efficiency of heat and mass transfer. Above deeper intrusions (>4 km), where fluid pressure is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…While the solubility of quartz is largely pHindependent in fluids with a pH below~9 (e.g., [37]), a value above that generally measured in primary geothermal fluids [58], quartz solubility depends strongly on salinity [18,39,43] and the concentrations of volatile gases such as CO 2 [42,43]. Phase separation of NaCl-rich water at temperatures above the critical temperature of pure water may lead to brine formation and halite precipitation [59], which may significantly reduce porosity and permeability near the intrusion [60]. Thus, these models are mainly appropriate for geothermal systems that are recharged by meteoric fluids and therefore contain dilute groundwater, rather than seawater.…”
Section: Geofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the solubility of quartz is largely pHindependent in fluids with a pH below~9 (e.g., [37]), a value above that generally measured in primary geothermal fluids [58], quartz solubility depends strongly on salinity [18,39,43] and the concentrations of volatile gases such as CO 2 [42,43]. Phase separation of NaCl-rich water at temperatures above the critical temperature of pure water may lead to brine formation and halite precipitation [59], which may significantly reduce porosity and permeability near the intrusion [60]. Thus, these models are mainly appropriate for geothermal systems that are recharged by meteoric fluids and therefore contain dilute groundwater, rather than seawater.…”
Section: Geofluidsmentioning
confidence: 99%
“…The basal parts of sheeted dyke complexes within the Troodos ophiolite contain elongated (up to 1 km wide), pod-shaped, quartz-rich epidosites [67], similar to the quartz-rich, low permeability zones that form in our simulations with initially high permeability host rocks (see Figure 9(c)). However, the dynamics of quartz precipitation in subseafloor hydrothermal systems containing seawater as the pore fluid will differ from systems containing pure water because of phase separation at temperatures above the critical point of pure water, brine formation, and halite precipitation [18,59,60].…”
Section: Comparison With Naturalmentioning
confidence: 99%
“…Scott et al (2016) modeled the temporal evolution of high enthalpy geothermal systems associated with shallow intrusions, and observed that host rock permeability and composition, intrusion depth, intrusion geometry, and strain rate all play important roles in the thermal structure. Scott et al (2017) noted that, for saline hydrothermal systems, the depth of the magmatic intrusions powering geothermal systems impacts the efficiency of heat transfer. In their models, for intrusions >4 km deep, heat transfer is maximized by phase separation occurring via condensation, whereas less efficient heat transfer occurs via boiling in shallower (<2.5 km) systems.…”
Section: Conceptual Models and Numerical Simulation Studiesmentioning
confidence: 99%
“…In large Mexican epithermal silver deposits of intermediate sulfidation state, Wilkinson et al [26] suggested that the ore forming fluids, were injected into a geothermal circulation system in response to the ascent of a magmatic intrusion. Such hydrothermal diapirs would be sourced from a stratified hyper-saline brine reservoir, formed in response to incremental exsolution of magmatic fluid, and intense brine condensation at depth, with halite precipitation, being stored above the source magma reservoirs [26,192,193]. By contrast, Essarraj et al [40,41,49] suggested that the ore-forming fluids were related to deep-basinal sedimentary brines and that metals had no genetic relationship with Neoproterozoic magmatism, on the basis of numerous deposits they investigated in the Eastern and Central Anti-Atlas.…”
mentioning
confidence: 99%
“…We here suggest that all ore deposits described above are related to the Ediacaran magmatic-hydrothermal complex emplaced from 575 to 530-520 Ma. The concept of stored hypersaline brines is emphasised following Scott et al [193]. Nevertheless, while a magmatic origin of such stored brines is obvious, the origin for Ca-rich brines has yet to be defined.…”
mentioning
confidence: 99%